From Stress to Costress : Stress Testing Interconnected Banking Systems - Maino, Rodolfo (IMF Working Papers; Working Paper, 2012)
This paper presents an integrated framework for assessing systemic risk. The framework models banks' capital asset ratios as a function of future losses and credit growth using a generalized method of moments to calibrate shocks to credit quality and credit growth. The analysis is complemented by a simple measure of systemic risk, which captures tail risk comovement among banks in the system. The main contribution of this paper is to advance a simple framework to integrate systemic risk scenarios that assess the impact of aggregate and idiosyncratic factors. The analysis is based on CreditRisk+, which uses analytical techniques-similar to those applied in the insurance industry - to estimate banks' credit portfolio loss distributions, making no assumptions about the cause of default.